32.5k views
4 votes
a) How would you write `\left(9^{-2}\right)\left(3^{11}\right)\left(\sqrt[3]{27}\right)` as a single pow

a) How would you write `\left(9^{-2}\right)\left(3^{11}\right)\left(\sqrt[3]{27}\right-example-1
User Bharathi
by
4.5k points

1 Answer

4 votes

Step-by-step explanation:

Given;

We are given the expression shown below;


(9^(-2))(3^(11))(\sqrt[3]{27})

Required;

We are required to express this as a single power.

Step-by-step solution;

To do this we would begin by applying some basic rules of exponents;


\begin{gathered} If: \\ a^b* a^c \\ Then: \\ a^^(b+c) \end{gathered}

Applying it to the first two parts of the expression, we will have;


\begin{gathered} (9^(-2))=(3^2)^(-2) \\ \end{gathered}
(3^2)^(-2)(3^(11))=3^(-4)*3^(11)
3^(-4)*3^(11)=3^((-4+11))
=3^9

We will also simplify the right side of the expression as follows;


\begin{gathered} If: \\ \sqrt[a]{b^c} \\ Then: \\ b^{(c)/(a)} \end{gathered}
\sqrt[3]{27}=27^{(1)/(3)}
27^{(1)/(3)}=(3^3)^{(1)/(3)}
\begin{gathered} If: \\ (a^b)^c \\ Then: \\ a^(b* c) \end{gathered}

Therefore;


(3^3)^{(1)/(3)}=3^{3*(1)/(3)}
3^{3*(1)/(3)}=3^1

We will now combine all parts of the expression and we'll have;


(9^(-2))(3^(11))(\sqrt[3]{27})
=3^9*3^1
=3^(9+1)
3^(10)

Also we are given the expression:


3^y5^y
\begin{gathered} If: \\ a^b* c^b \\ Then: \\ (a* c)^b \end{gathered}

Therefore;


3^y5^y=(3*5)^y
15^y

Therefore;

ANSWER:


\begin{gathered} (a) \\ 3^(10) \end{gathered}
\begin{gathered} (b) \\ 15^y \end{gathered}

User Zhambul
by
4.8k points